CO2 methanation over metal catalysts supported on ZrO2: Effect of the nature of the metallic phase on catalytic performance. (10th August 2021) - Alves, Lizandra M.N.C.; Almeida, Mayra P.; Ayala, Martin; Watson, Caleb D.; Jacobs, Gary; Rabelo-Neto, Raimundo C.; Noronha, Fabio B.; Mattos, Lisiane V.
Graphical abstract: Highlights: Ni/ZrO2, Ru/ZrO2 and Ni-Ru/ZrO2 catalysts were tested for CO2 methanation. The formation of an alloy was detected for bimetallic catalysts. Ru/ZrO2 was the most active catalyst with a reaction rate of 1.35 mol/molmetal .s. Ru/ZrO2 exhibited a CH4 selectivity of 97.3% and the highest stability. A mechanism for CO2 methanation was suggested by in situ DRIFTS analyses. Abstract: Zirconia was used to support Ru, Ni, and Ru-Ni bimetallic nanoparticles for CO2 methanation. The formation of an alloy was detected in Ru K-edge spectra. The Ru/ZrO2 exhibited the highest CO2 reaction rate (1.35 mol/molmetal .s) with a CH4 selectivity of 97.3%. The diffuse reflectance infrared fourier transform spectroscopy experiments suggest that formates serve as intermediates in converting CO2 to CO via reverse water–gas shift at the interface between Ru and defect-sites on zirconia, while Ru metal intercepts CO, further hydrogenating it to CH4 . The better performance of Ru/ZrO2 could be related to the Ru-zirconia interface and Ru on-top atoms, which promote the reverse water gas shift and the CO hydrogenation reactions. Thus, this work provided important information about the effect of alloying Ru with Ni on the performance of the catalyst for the CO2 methanation, as well as the mechanism of this reaction for the best catalyst, Ru/ZrO2 .